ALTERNATIF MEDIASI PENAL DALAM SISTEM PERADILAN PIDANA DI INDONESIA - Reyner .; Dian Andriawan Daeng Tawang (Jurnal Hukum Adigama, 2018)
In general, penal mediation can be said as a concept that brings together the victims and criminals to discuss their interests and willingness in order to resolve criminal cases that have occurred between them, and are assisted by a mediator who is neutral and help to resolve criminal cases by giving advice and mediating as mediators. The results of the research conducted by normative research and through several literature such as legal books, regulations, and guidelines, show that in fact, reason mediation has been carried out in the community and carried out by several law enforcement officials in the framework of the settlement process criminal. What is done in the midst of Indonesian society is only a peace process that shows customary law as its branch and many are applied within the police in the investigation process to carry out procedures for resolving criminal acts. The importance and need for penal mediation to be applied in formal law that is developing and prevailing in society can be a special rule that is regulated and is part of criminal procedural law for the sake of legal certainty. Penal mediation can be applied at the level of investigation by the police in the process of resolving criminal cases and creating equal welfare and justice in the wide society for sure